PIDANA MATI SEBAGAI SARANA EXTRA ORDINARY DALAM MEMBERANTAS TINDAK PIDANA KORUPSI - Haninah Mahfoedz (Jurnal Hukum Adigama, 2021)
Corruption is now increasingly rampant in this country and is very difficult to stop. Corruption has occurred in all areas of governance, be it executive, legislative, or judicial. The continuous increase in corruption in Indonesia causes this crime to be included in the category of extraordinary crime or known as extraordinary crime. The consequences that occur when corruption is categorized as an extraordinary crime are that it must be handled in extraordinary ways and even though it is normative, Article 2 paragraph (2) of the Corruption Law which allows for a death penalty for committing corruption in certain circumstances, Until now, since the AntiCorruption Law was passed, no perpetrator has been sentenced to the death penalty. Even for corruption committed during the pandemic, no one was sentenced to death. Thus, the problem in this research is how to reformulate the death penalty provisions in the criminal law policy of corruption in the future by using normative legal research (normative juridical) or prescriptive library law research.